Pengaruh Disiplin, Motivasi dan Kepuasan terhadap Kinerja Personil di Korem 101 Antasari Banjarmasin - Faizal Maulidhany Rarin; Teguh Yuda Prakosa (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
The aim of the study was to find out: Conditions of discipline, motivation, satisfaction and performance of Personnel at Korem 101 Antasari Banjarmasin Influence of Discipline on Personnel Performance at Korem 101 Antasari Banjarmasin Influence of Motivation on Personnel Performance at Korem 101 Antasari Banjarmasin Influence of Satisfaction on Personnel Performance at Korem 101 Antasari Banjarmasin Influence Discipline, Motivation and Simultaneous Satisfaction with Performance The population of this study were all Korem 101/Antasari personnel totaling 289 people, 261 people for the Military and 28 Korem civil servants. The number of samples that we will use by calculating the slovin formula is 75 people